Media and culture-based public in the quadruple helix innovation model - Slobodan Cvetanović; Andrea Andrejević Panić; Simonida Vukadinovic (BizInfo)
Spiral innovation models challenge the technological and economic determinism inherent in linear "science and technology push" and "demand pull" frameworks that explain the primary drivers of innovation. These models posit that innovation is a multifaceted phenomenon, shaped by socio-economic contexts and cultural-historical legacies. The Quadruple Helix model extends the foundational Triple Helix by integrating civil society as a fourth dimension alongside academia, industry, and government. This expanded model emphasizes the interplay between these actors and civil society in shaping demands for innovative solutions in products and services. Civil society, as a multi-layered concept, encompasses media, culture, social values, lifestyles, art, and democratic principles. This paper critically examines the role of the culture- and media-based public and the inherently ambivalent nature of civil society within the Quadruple Helix model. By exploring their influence on the commercialization of knowledge into innovation, the analysis underscores the theoretical and practical implications of this extended framework.